PERKEMBANGAN EKONOMI GLOBAL - Drs Hafulyon (JURIS (Jurnal Ilmiah Syariah), 2018)
Countries in the world face different forms of economic developments in the field of regional trade, domestic and international, the United States dollar increase in events that coincide with the occurrence of a deficit in trade balance and current transactions, result in unemployment accompanied by high inflation, a flexible exchange rate system is not able to stimulate the growth of global trade and a range of economic growth. This fact cannot be separated from some of the economic concept of development as the paradigm adopted in the design of economic policy because the experts were trying to trace back the development of economic concepts, which gave birth to a new paradigm that is different from the previous paradigm.